SEROLOGIC DETECTION OF EHRLICHIA CANIS AND EHRLICHIA CHAFFENSIS IN STAFF OF VETERINARY CLINICS IN LIMA - Paulino R., Analí (2013)
The aim of the present study was to detect seropositivity against Ehrlichia canis and Ehrlichia chaffeensis in staff of veterinary clinics and in persons that had contact with dogs affected by canine ehrlichosis using the indirect immunofluorescence test. Ninety serum samples were used, 55 men and 35 women. Results indicated 23.3% of seropositivity to E. canis and 20.0% to E. chaffeensis, without statistical differences due to gender.